Consumer Behaviour towards Instant Food Products - Ramasamy, A. K.; Kalaivanan, G.; Sukumar, S. (Indian Journal of Marketing, 2005)
Energy is required for sustaining all forms of life on earth and so food is the basic need of a man for his survival. The primitive man was largely dependent for his food on fruits and animals. The discovery of fire marked a turning point in the process of civilization and man has learnt to cook food. During the course of time, the man changed his food habits according to his taste, experience, and availability of food materials and changing vessels, equipments and tools but still people were in search of new techniques to speed up the cooking process in order to cope up with mechanical life, as they do not have sufficient time to cook food in the conventional methods. So the modern men and women hard pressed for time have to yield themselves to the fast changing life styles as regards cooking and food habits. In the ever-changing socio-domestic scenario, both men and women have to necessarily go for employment to augment the household income and cooking food in traditional method is really an ordeal for women.